The fate of river-borne contaminants in the marine environment: Characterising Regions of Freshwater Influence (ROFIs) and estuary plumes using idealised models and satellite images. (July 2020) - Hunt, Stephen; Jones, Hannah F.E.
Abstract: A combination of idealised modelling and satellite imagery has been used to assess the dispersal of estuarine plume water and suspended material throughout the ecologically significant marine area off the west coast of the central North Island, New Zealand. The idealised modelling was used to elucidate the relative importance of oceanographic and meteorological conditions in controlling the horizontal structure of the estuary plumes, and then compared to plumes visible in satellite imagery and environmental monitoring data. Under low to average river flows the plumes can be categorised as either non-rotational or rotational. Rotational plumes are directed southwards under light (<5 m/s SW or <10 m/s E) winds and northwards under stronger (>5 m/s SW) winds. Non-rotational plumes remain close to the estuary mouth. The type, orientation and extent of the plumes have implications for estuarine flushing and for the dispersal of land-derived contaminants into the marine environment. Highlights: Plume extent has been described using a combination of satellite imagery and models. The methods provide a coherent explanation of plume extent. Plume extent controls estuarine flushing and the distribution of contaminants.